(untitled) (Ameghiniana, 2013)
"A new Ordovician bivalve fauna is described: Cadomia typa De Tromelin, Cocloconcha cf. C. oblonga Foerste, Cyrtodontula sp. and Malletiidae and Edmondiacea were recognized. The evídences of thís fauna and the associated Genus Brongniartella (Trilobita ) suggest a maximal Llandeilian age for the upper mid-portion of the Santa Gertrudis Formation.